Revealing Cathode–Electrolyte Interface on Flower‐Shaped Na3V2(PO4)3/C Cathode through Cryogenic Electron Microscopy. Issue 10 (31st May 2021) - Ihsan-Ul-Haq, Muhammad; Cui, Jiang; Mubarak, Nauman; Xu, Mengyang; Shen, Xi; Luo, Zhengtang; Huang, Baoling; Kim, Jang-Kyo
Abstract : The electrode–electrolyte interfaces play a critical role in influencing the cyclic stability, Coulombic efficiency, and safety of rechargeable batteries. Although there are many recent efforts for investigating the solid electrolyte interface formed on anodes, much less attention has been paid to examine the cathode–electrolyte interface (CEI) established on cathodes. Understanding of the chemistry, morphology, and structure of CEI layers is still illusive requiring further in‐depth characterization. The cryogenic electron microscopy is used to reveal a 1.1 nm thick CEI layer formed on a flower‐shaped, carbon‐coated Na3 V2 (PO4 )3 /C (NVP/C) cathode in ether‐based electrolyte for Na‐ion batteries. The rationally designed NVP/C cathode delivers cyclic stability with a capacity retention of over 88% at 50 mA g −1 after 1600 cycles and an excellent high‐rate capability at up to 3200 mA g −1 . These findings may shed new light on the design of CEI layers to achieve high energy and power densities in rechargeable Na‐ion/metal batteries. Abstract : The cryogenic electron microscopy is used to examine the cathode–electrolyte interface (CEI) on a carbon‐coated flower‐shaped Na3 V2 (PO4 )3 (NVP/C) cathode for Na‐ion batteries in ether‐based electrolyte. A conformal CEI layer of 1.1 nm in thickness is revealed. The NVP/C cathodes demonstrate excellent cyclic performance with 88% capacity retention after 1600 cycles and a high‐rate capability for up to 3200 mA g −1 .